THE ROLE OF FORMAL, NON-FORMAL AND INFORMAL EDUCATION IN THE POLITICAL FORMATION OF WOMEN EDUCATORS - Lima, Edwiges Inacia de [UNESP]; Alves Nagao, Fernanda Quinei [UNESP]; Selmo, Jaqueline Tumitan [UNESP]; Paz Landim, Sorrana Penha [UNESP]; Machado Lima, Vanda Moreira [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2019)
This article aims to understand the role of formal, non-formal and informal education in the training of three women who have an active participation in social movements and unions. The methodology used was semi-structured interview and bibliographic research, which enabled us to have an understanding about the subject to observe the reflexes of this in the life of the interviewees. We conclude that formal education was very important in the lives of the interviewees and that they consider such importance for the rise of the context from which they came, however, it is possible to observe the relevance of experiences in non-formal and informal education, where they experienced a different education, with learning and practical values of how to participate politically by acting democratically.
Keywords: Political formation; Formal education; Non-formal education; Informal education